The Principal's Role In Maintaining Teacher Commitment Through Quality Culture After The Covid-19 Pandemic - Ramadhani, Khalilah; Hariyadi, Aburizal Sofwan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Education is currently in a new state after Covid-19, which has brought changes to education. Especially in the competence of teachers whose development is highly demanded to face the normal era. This study aims to reveal the role of school principals in improving the ability of teachers, so that teacher commitment can be maintained through a school quality culture. This study uses a library research research method by using documentation data collection techniques from several references and the analysis is carried out using descriptive analysis methods. The results obtained that school principals can carry out strategies to increase teacher commitment in the normal era through attention to improving the quality of learning, fulfilling infrastructure, increasing teacher professionalism, forming work teams, giving authority to regulate good learning flows to teachers, establishing collaboration with outside parties, providing rewards to teachers, to evaluations that build teacher commitment.